Novel SARS-CoV-2 and COVID-2019 Outbreak: Current Perspectives on Plant-Based Antiviral Agents and Complementary Therapy - Gezici, Sevgi; Sekeroglu, Nazim (Indian Journal of Pharmaceutical Education and Research, 2020)
The Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) caused the novel Corona Virus Disease 2019 (COVID-19), which has been defined as a pandemic by the World Health Organization (WHO) in 2020. The rapid global spread of SARS-CoV-2 virus as a global health emergency has emphasized to findeffective treatment strategies in clinical trials. The several drug trials including Lopinavir (LPV) and Ritonavir, Chloroquine (CLQ), Hydroxychloroquine, Favipiravir (FPV), Remdevisir (RDV), Nitazoxanide, Ivermectin and Interferon, have been explored in COVID-19 patients and some of the drugs have been waiting clinical approval for their anti-SARS-CoV-2 activities. Clinical trials are still ongoing to discover promising new multidrug combination treatment for COVID-19 patients. Considering the difficulties to ascertain efficient drug candidates and the lack of specific anti-viral therapies against COVID-19 outbreak, the current management of SARS-CoV-2 should mainly be supportive. From this point of view, enhancing the immune system through medicinal plants with wide range of bioactive compounds, which exhibit antiviral activities, can play significant roles to increase defense barrier in COVID-19 patients. On the other hand, plant-based agents as complementary and alternative therapies have potential advantages to reduce symptoms of this life-threatening disease and could promote the public health. Recently, there has been a remarkable progress in the field of antiviral herbal therapy owing to increasing concerns about the development of drug resistance and limited advances in the field of antiviral drug discovery. This review provides an overview of published information onbiology, genomic structure, replication cycle and pathogenesis of SARS-CoV-2. It also aims to assemble the fact and a scientific intellectual groundwork on development of antiviral herbal therapy on the bases of extensive literature collection.
Keywords: SARS-CoV-2; COVID-19; Outbreak; Medicinal plants; Antiviral